2003
DOI: 10.1038/sj.onc.1206748
|View full text |Cite|
|
Sign up to set email alerts
|

Real-time imaging of TRAIL-induced apoptosis of glioma tumors in vivo

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has been shown to induce apoptosis in neoplastic cells. While many previous studies have been performed in cell culture, the delivery and efficiency of TRAIL variants in vivo is less well established. Using dual substrate/ reporter bioluminescence imaging (Fluc: firefly luciferase -luciferin and Rluc: Renilla luciferase -coelenterazine), we tested the efficacy of TRAIL using replicationdeficient herpes simplex virus (HSV) type 1 amplicon vectors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(84 citation statements)
references
References 36 publications
2
81
0
1
Order By: Relevance
“…As opposed to systemic delivery of therapeutic agents, MSCs have the advantages of offering a continuous and concentrated local delivery of secretable therapeutic molecules like TRAIL, thus reducing the non-selective targeting, and allowing higher treatment efficiency and potency for a longer time period. A number of previous studies by others and ourselves (4,13,14,44,45) have shown that in vivo bioluminescence imaging of tumor cells enables rapid, noninvasive measurement of tumor load before, during, and after treatment of mice with highly malignant intracranial tumors. Despite the advantages and convenience of bioluminescence imaging for monitoring tumor growth, there are some disadvantages that should be taken into account while assessing the fate of tumors in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to systemic delivery of therapeutic agents, MSCs have the advantages of offering a continuous and concentrated local delivery of secretable therapeutic molecules like TRAIL, thus reducing the non-selective targeting, and allowing higher treatment efficiency and potency for a longer time period. A number of previous studies by others and ourselves (4,13,14,44,45) have shown that in vivo bioluminescence imaging of tumor cells enables rapid, noninvasive measurement of tumor load before, during, and after treatment of mice with highly malignant intracranial tumors. Despite the advantages and convenience of bioluminescence imaging for monitoring tumor growth, there are some disadvantages that should be taken into account while assessing the fate of tumors in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…료의 효과를 정략적으로 분석하거나 [10] 줄기세포(stem cell) 치료 후 이식편의 생존율(graft Survival)을 분석 [11] 하는 등의 실험에 유용하게 사용될 수 있다. 세포에 삽입된 루시페라제가 루시페린을 만나서 방출하는 빛 의 양(photon counts)이 세포의 수에 비례한다 [12] .…”
Section: 본 논문에서는 분자영상의 종류와 분자영상의 적용unclassified
“…Taking advantage of the efficient tumor targeting capabilities, investigators have used genetically engineered NSCs to disseminating tumors. Genetically modified NSCs from different sources have been shown to exhibit the same gliomatropic effect in gliomabearing models and effectively to reduce tumor bulk and prolong host survival [13][14][15][16][17][18][19] .…”
Section: Exogenous Stem Cells Tropism For Gliomasmentioning
confidence: 99%
“…This behavior of NSCs has been exploited as a tumor targeting strategy for glioma gene therapy [11][12][13][14][15][16][17][18][19] . Recently, it has been suggested that mesenchymal stem cells (MSCs) may represent an alternative source of NSCs for regeneration [20,21] .…”
Section: Introductionmentioning
confidence: 99%